BMBF-Projekt „Körper und Malerei“: Erschließung, Erforschung und Nutzung der Anatomischen Lehrsammlung und der Gemäldesammlung der Hochschule für Bildende Künste Dresden - Sandra Mühlenberend; Jakob Fuchs; Ivo Mohrmann (In Situ)
Dresden University of Fine Arts (HfBK) is, with the École nationale des beaux-arts de Paris, one of the two academies of Fine Arts in Europe that possesses an old and very rich collection for artistic anatomy. The anatomy collection of Dresden University of Fine Arts has been built up since the beginning of the 20th century and constantly expanded. It comprises today nearly 700 anatomic models and specimens of human and animal anatomy. Thanks to those numerous specimens and ancient models, teachers developed in the 20th century their own educational material and methods whose value had been recognized far beyond the frontiers of the HfBK Dresden. After 1989, the old models and specimens lost their importance; the collection was hardly used for teaching and its condition had deteriorated. It was only in the late 1990’s that the immense value of the collection was rediscovered, and that the first protective measures were taken and the first studies were carried out. The collection was first removed completely from active teaching material and placed in a storage room. Since then, those fonds have been the focus of research in art history and conservation. From February 2017 to January 2020, a project financed by the Federal Ministry of Education and Research aimed at making the collection available again for teaching, after all those years. On 6 November 2019, after three years of intensives research and projects, its reopening was celebrated.